The Impact of Virtual Field Experience during COVID 19 on Preservice English Language Teachers’ Classroom Management Perceptions and Concerns - ERTAN ALTINSOY (Journal of English Teaching, 2023)
This study is intended to reveal the virtual field experience of preservice English language teachers and investigate the impacts of Covid-19 enforced virtual field experience on the classroom management concerns and priorities of the participants. Within this scope, the present qualitative study included eight senior-year preservice English language teachers enrolled at a public university in Turkey and portrayed their three-month online practicum experiences by collecting data from reflective diaries, semi-structured interviews, and classroom observation records. The findings obtained by analyzing the data within the framework of grounded theory with the aid of qualitative data analysis software revealed that the virtual field experience process caused a serious impact on the classroom management concerns of the participants that were observed to be communication-oriented, lesson planning and instruction oriented, discipline-oriented and learner and teacher-oriented aspects. The findings further revealed that virtual field experience increased the participants' concerns about professional development which implied that it could be used as an alternative if it is revised and redesigned